2022
DOI: 10.1002/vnl.21897
|View full text |Cite
|
Sign up to set email alerts
|

Facile construction of flame‐retardant, heat‐insulating agar/polyvinyl alcohol composite aerogels via in situ formation of magnesium hydroxide and palygorskite‐assisted strategy

Abstract: Natural polymer aerogel is a candidate material with broad application prospects in the field of building insulation because of its lightweight, low thermal conductivity, and biodegradability. However, poor mechanical properties and easy combustion greatly limit its development. In this work, magnesium hydroxide (MH) was synthesized in situ in the agar (AG)/polyvinyl alcohol (PVA) composites using magnesium oxide as raw material. Furthermore, the one-dimensional rod-like nanoclay palygorskite (Pal) was introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…11,12 From the last decade, numerous nanofillers such as halloysite nanotubes (HNT), montmorillonite clay (MMT), nanocarbon based graphene, carbon nanotubes (CNT), aluminum trihydrate (ATH), Ti 3 C 2 T x (MXenes) and 2D materials have been used to improve the thermal stability of polymers. [13][14][15][16] However, improving the thermal and dielectric properties is still very challenging due to weak interfacial strength, delamination, poor dispersion, polarity, and nature of fillers and their percolation limit. [17][18][19] Among various nanostructures, LDH (double layered hydroxides) has received wide popularity as ecofriendly and biocompatible inorganic filler due to their unique properties such as high thermal stability ($500 C), high dielectric constant, ion-exchange property, high absorption, high aspect ratio and fireretardant behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 From the last decade, numerous nanofillers such as halloysite nanotubes (HNT), montmorillonite clay (MMT), nanocarbon based graphene, carbon nanotubes (CNT), aluminum trihydrate (ATH), Ti 3 C 2 T x (MXenes) and 2D materials have been used to improve the thermal stability of polymers. [13][14][15][16] However, improving the thermal and dielectric properties is still very challenging due to weak interfacial strength, delamination, poor dispersion, polarity, and nature of fillers and their percolation limit. [17][18][19] Among various nanostructures, LDH (double layered hydroxides) has received wide popularity as ecofriendly and biocompatible inorganic filler due to their unique properties such as high thermal stability ($500 C), high dielectric constant, ion-exchange property, high absorption, high aspect ratio and fireretardant behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the size, shape, dispersion and the chemistry of the nanofiller strongly influence the thermal stability and dielectric properties of polymers 11,12 . From the last decade, numerous nanofillers such as halloysite nanotubes (HNT), montmorillonite clay (MMT), nanocarbon based graphene, carbon nanotubes (CNT), aluminum trihydrate (ATH), Ti 3 C 2 T x (MXenes) and 2D materials have been used to improve the thermal stability of polymers 13–16 . However, improving the thermal and dielectric properties is still very challenging due to weak interfacial strength, delamination, poor dispersion, polarity, and nature of fillers and their percolation limit 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…The low flame‐retardant efficiency of MH, which has become a pressing issue that needs to be addressed 19–21 . Additionally, because of the high interfacial energy and strong hydrophilicity of MH, it exhibits poor compatibility with the polymer matrix, which greatly destroys the mechanical properties and machinability of matrix material 22–24 …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Additionally, because of the high interfacial energy and strong hydrophilicity of MH, it exhibits poor compatibility with the polymer matrix, which greatly destroys the mechanical properties and machinability of matrix material. [22][23][24] Synergistic flame retardants can be used to simultaneously reduce the amount of MH added to the polymer material and improve the low flame retardancy efficiency of MH. Synergistic flame retardants include zinc borate (ZB), black phosphorus, graphene, carbon nanotubes (CNTs), and so forth.…”
mentioning
confidence: 99%